Analysis of profitability ratio to financial performance of Indonesian telecommunication company Tbk (2018-2022 Period) - Lestari, Puji; Rafiyani, Ade Repi; Rahmawati, Siti Nur; Haryadi, Didit (Trigin Publisher, 2024)
This study aims to assess the financial performance of PT Telekomunikasi Indonesia Tbk by analyzing financial statements using profitability ratios. Data collection techniques in this study use qualitative research methods with a descriptive approach. The type of data in this study is secondary data, which is obtained directly through the official website of PT Telekomunikasi Indonesia Tbk. This research received the results of the profitability ratio at PT Telekomunikasi Indonesia Tbk; namely, the development of the company's ratio cannot be said to be good because it has decreased a lot from year to year. This causes the company to be unable to generate profits because the calculation of return on assets, return on equity, gross profit margin, and net profit margin every year has decreased significantly. However, the same increase in 2021 also decreases again the following year. So it can be said that the company has not been efficient in generating profits and its financial performance also cannot be said to be good. This study aims to develop a model for reviewing financial statements from financial performance. This research is expected to make theoretical contributions to the literature in this context, including in the context of financial and banking management.